Tribological performance of jatropha oil-based nanofluids for orthogonal cutting process - Jamaluddin, Nor Athira (2021)
The increasing awareness and concerns toward the environmental and health issues have risen the attention to shift the petroleum-based metalworking fluids (MWFs) toward the use of renewable and biodegradable energy sources for the production of MWFs. Thus, vegetable-based MWF, especially crude jatropha oil (CJO) is considered as a great potential substitution of the petroleum-based oil. However, the crucial limitation of using CJO is low thermal and oxidation stability that leads to poor lubrication behaviour. Hence, the aim of this study was to develop and evaluate the nanofluid formulations from modified jatropha oil (MJO) as the MWF. The MJOs were formulated from jatropha methyl ester with addition of trimethylolpropane (JME: TMP) at molar ratio 3.5:1 through transesterification process. Subsequently, the MJOs were mixed with hexagonal boron nitride (hBN), graphene and copper oxide (CuO) nanoparticles at various concentrations (i.e. 0.01 to 0.05 wt.%). The performance of MJOs was analysed based on the physicochemical properties, tribological behavior and orthogonal cutting. According to the current findings, thermal-oxidation stability of MJOg3 (MJO+0.05wt.% graphene nanoparticles), MJOh3 (MJO+0.05wt.% hBN nanoparticles) and MJOc3 (MJO+0.05wt.% CuO nanoparticles) were significantly improved by achieving the highest viscosity index among the other studied samples. Contrastingly, MJOh2 (MJO+0.025wt.% hBN nanoparticles), MJOg2 (MJO+0.025wt.% graphene nanoparticles) and MJOc2 (MJO+0.025wt.% CuO nanoparticles) provided the lowest coefficient of friction, friction torque, mean wear scar diameter, surface roughness, volume wear rate and smoothest worn surfaces. For orthogonal cutting process, MJOh2, MJOg2 and MJOc2 offered the lowest cutting temperature, chip thickness and tool-chip contact length. In summary, the MJO with moderate concentration of nanoparticles (MJOh2, MJOg2, MJOc2) provided a superior tribological and machining performance which was a highly potential substitution to the synthetic ester (SE) for the green machining process.